Children’s Book Design and Illustration in Poland, c. 1968 - Anita Wincencjusz-Patyna (Strenae)
The paper gives an overview of children’s book design and illustration in Poland around the year 1968. Considering the number, variety and quality of books addressed to young readers of this time, one can judge how important this sector of the reading audience was for the policymakers in the times of Polish People’s Republic (1952-1989). The graduates from academies of fine arts (predominantly from Warsaw) were responsible for illustrations and design of the released titles. 1968 seems to be the peak year of the internationally recognized Polish School of Illustration. More than 400 artists were active in the field of book illustration at that time. Among the published books there were many avant-garde and original designs. However, this tendency was already present in Polish graphic design in the 1950s, with a sort of a turning point in 1956. The year 1968 was very important in Polish history and brought some political and social changes, although these were not reflected that much in fine and applied arts. The paper discusses artistic quality of Polish illustration for children published around the year 1968. The short analyses of the relevance of graphic layout and illustrations to the verbal contents of the selected books comprises the main part of the paper.